The Effectiveness Of The Credit Relaxation Policy On The Batik MSMEs Affected By Covid-19 In Solo City - Edy Supriyono; Nurmadi Harsa Sumarta (Jurnal Akuntansi dan Pajak, 2021)
This research focuses on empirical analysis of the effect of credit relaxation policy on the sustainability of Batik MSMEs in Solo. This research is motivated by the negative impact of the spread of the Corona virus (Covid-19) pandemic on the economic sector in Solo, especially in the Batik MSMEs, which is one of the mainstay affected industries. A more in-depth study of the effectiveness and influence of this implementation on the sustainability of batikMSMEs in the city of Solo is needed, especially from the perspective of direct MSMEs. The design of this research is causality research with the object of batik UMKM in the administrative area of Surakarta City. The data used are primary data from questionnaires. Data analysis will be performed with Multiple Regression Analysis. With this research, it is hoped that there will be a contribution to increasing the effectiveness of the implementation of credit relaxation at MSMEs if there is a similar urgent situation.